2016
DOI: 10.4149/km_2016_6_491
|View full text |Cite
|
Sign up to set email alerts
|

Corrosion resistance of surface treated 42CrMo4 steel

Abstract: This article deals with corrosion resistance comparison of plasma nitrided 42CrMo4 steel to another surface technologies used for breech mechanism manufacturing in the armament production. Increasing of demands on materials used for armament production and in other industrial applications leads to the innovation of technologies in the field of surface treatment, especially wear resistance, surface hardness, running-in properties and corrosion resistance, optical demands and others. For the evaluation of experi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…After 15 hours of plasma nitriding in the nitriding appliance the white layer with thickness oscillating around 4 µm covered the specimen´s surface. A significant porosity was not visible in the compound layer, hence the compound layer can also provide an enhancement of the surface´s corrosion resistance [17,18].…”
Section: Microstructurementioning
confidence: 99%
“…After 15 hours of plasma nitriding in the nitriding appliance the white layer with thickness oscillating around 4 µm covered the specimen´s surface. A significant porosity was not visible in the compound layer, hence the compound layer can also provide an enhancement of the surface´s corrosion resistance [17,18].…”
Section: Microstructurementioning
confidence: 99%
“…Li et al [13] found that in plasma nitriding of austenitic steel, the hardness achieved depends on the nitriding time. Nitrided layers are resistant to fatigue and wear and have good sliding properties and corrosion resistance [11,14].…”
Section: Introductionmentioning
confidence: 99%
“…And new nitriding technologies are continuously developed e. g active screen plasma nitriding (ASPN) to increase the effectivity of plasma nitriding, but not widely used in industry application (5). The plasma nitriding process is applied to ferrous materials (for all grades of steel, cast irons) has been extensively used to improve the surface properties (6), fatigue (7), corrosion (8), and also improve load-bearing capacity of dynamically loaded components friction and wear properties (9). However, it should be noted that some properties such as notch toughness may be reduced (10).…”
Section: Introductionmentioning
confidence: 99%